Diffuse lung disease in infants less than 1 year of age: Histopathological diagnoses and clinical outcome. Issue 10 (20th January 2015) - O'Reilly, Ruth; Kilner, David; Ashworth, Michael; Aurora, Paul
Summary: Introduction: Interstitial lung disease (ILD) in infants is rare. Clinical and radiological features are often non‐specific, and overlap with growth disorders and infection. In infants with severe respiratory compromise, lung biopsy is often necessary to guide acute management, but the risk and diagnostic yield of this procedure is incompletely understood. Aims: To retrospectively review infants undergoing open lung biopsy for suspected ILD at a large referral center; to determine morbidity and mortality related to the procedure; and to describe subsequent diagnosis and outcome. Methods: Lung biopsies performed in infants (aged <1 year) between January 1, 2005 and March 31, 2012 were identified and clinical data were collected. Biopsies were reclassified using the ChILD classification for diffuse lung disorders in infants. Results: Twenty‐seven infants were identified, with the number of biopsies performed increasing each year over the study period. There was no mortality and negligible morbidity associated with biopsy. Diagnoses seen were similar to those reported by the ChILD network. Histopathological diagnosis was not compatible with life in the absence of lung transplant in 6/27 (22%) of infants. Of the 14 children longitudinally followed up (median 0.5 (0.4 – 5.81) years), only four continued to require supplemental oxygen. Conclusion: Lung biopsy in infants with suspected ILD is safe, and histopathological diagnosis frequently assists treatment decisions, particularly with regard to withdrawal of care.Pediatr Pulmonol. 2015; 50:1000–1008. © 2015 Wiley Periodicals, Inc.